2022
DOI: 10.1108/imefm-01-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

Infaq during movement lockdown: the perspective from social responsibility theory

Abstract: Purpose Within a few days, the National Disaster Management Agency’s COVID-19 Fund (NADMA) has collected RM 5.5 m in donations from individuals and companies. These data shows that voluminous Malaysians are willing to help although they are in a difficult situation. Grounded in the Social Responsibility theory, this paper aims to examine the factors that motivate infaq (donation) behaviour in Malaysia during Movement Control Order (MCO). Design/methodology/approach The quantitative questionnaire survey metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
2
0
2
Order By: Relevance
“…Smith and Mcsweeney (2007), and Manstead (2000) reported that moral norms are an important predictor of prosocial behaviors. Jalil et al,'s (2022) study showed that the stronger the moral norm of helping others in an emergency, the higher the probability that Muslims will infaq. This study supports the proposition that for moral norms to impact behavior, they must be activated by the desire to assist others for a noble cause as part of worship, seeking Allah's pleasure and rewards in the Hereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Smith and Mcsweeney (2007), and Manstead (2000) reported that moral norms are an important predictor of prosocial behaviors. Jalil et al,'s (2022) study showed that the stronger the moral norm of helping others in an emergency, the higher the probability that Muslims will infaq. This study supports the proposition that for moral norms to impact behavior, they must be activated by the desire to assist others for a noble cause as part of worship, seeking Allah's pleasure and rewards in the Hereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this study, 7 variables were analyzed as measured by measurements adopted from Jalil et al (2022;Berakon et al 2021;Aji et al 2020)…”
Section: Research and Methodologymentioning
confidence: 99%
“…Hasil yang telah didapat pada gambar diatas adalah hal ini menunjukkan bahwa sebaran data mengikuti arah garis dan memanjang mengelilingi garis lurus, maka garis tersebut menunjukkan terdistribusi normal (Jalil, 2022). Sumber: Data Primer diolah 2023…”
Section: Gambar 1: P-plotunclassified